Homomorphic signature schemes for single-source and multi-source network coding - Huifang YU; Wen LI (Tongxin xuebao)
To solve the problems of pollution attacks of single-source and multi-source network coding,two homomorphic signature schemes for network coding were proposed.In homomorphic signature for single-source network,the message hash value was signed on the elliptic curve,then the message,hash value and the signature of hash value were output,and the receiving node could verify the signature,the elliptic curve signature based on homomorphism could resist intra/inter-generation pollution attacks.Homomorphic signature from pairings for multi-source network coding could resist pollution attacks,and the introduction of timestamp made it be capable to resist replay attacks.In the random oracle model,it proves that two schemes are all secure under the selective attacks.Analysis shows that two schemes can effectively improve the verification efficiency.